Existentialist Roots of Narrative Actants - David Herman (Studies in 20th & 21st Century Literature, 2000)
It is time to rethink the history of narratology, a field of study that is undergoing a recontextualization and renaissance. Examining ways in which classical narrative theory was embedded in its cultural milieux, this paper reconsiders one chapter in the history of structuralist narrative analysis as it emerges in France in the 1960s. The paper focuses on the genesis—and the genealogy—of the concept of narrative "actants." Actants were originally construed as names for the basic and general roles that can be assumed by characters in the unfolding of a narrative. Structuralist theories owed much to Vladimir Propp's actantial typology, which included the villain, the donor, the helper, the sought-for-person and her father, the dispatcher, the hero, and the false hero. But existentialist theories of the self may also have inflected the way structuralist narratologists drew on linguistic theory to redescribe characters in stories as actants. Further, a more historically particularized account of actants may have significant methodological consequences for present-day analysts interested in using actantial models to study narrative.
Keywords: narratology; existentialism; classical narrative theory; structuralist narrative analysis; narrative actants; Vladamir Propp; actactial typology; existentialist theory; narrative study